Exploring Technology-Driven Simulations in Practical Physics: Insights into Mechanical Measurements Concept - Kade, Amiruddin; Supriyatman, S.; Kamaruddin, Abdul; Novia, N.; Supriyadi, S.; Husain, Sadang (Universitas Pendidikan Indonesia (UPI), 2024)
This study aimed to explore the effectiveness of technology-driven simulations in improving high school students' practical skills in mechanical measurement within the context of physics education. A quasi-experimental design was employed, involving control groups and pretest-posttest samples to assess students' understanding and application of mechanical measurement concepts. The results indicate that simulations significantly enhance students' accuracy and comprehension of mechanical measurements compared to traditional teaching methods. Notably, visual and kinesthetic learners benefit the most from using simulations prior to engaging in physical experiments. The combination of simulations and hands-on experiments was found to be more effective in developing practical skills than either approach alone. These findings underscore the value of integrating technology-driven simulations into physics curricula, particularly for enhancing learning outcomes and practical skills in mechanical measurement, with a specific advantage for learners with visual and kinesthetic preferences.